Upaya Menyikapi Bentuk Kaidah Komitmen pada Perspektif Anggota Organisasi dalam Pengelolaan Organisasi Bidang Kemaritiman - Khamdilah, Ali; Utami, Tini; Rubiyanto, Aan; Pambudi, Pambudi (Politeknik Bumi Akpelni, 2024)
Abstract The purpose of this study is to determine the extent of the perspective of organizational members about the meaning of commitment to organizational management. With the background, namely the mindset of organizational members in interpreting the form of commitment to organizational management, the main problem that arises is the inability to interpret the form of actual commitment that is based on organizational members including understanding commitment, realization of commitment, commitment obstacles, so that it becomes a dilemma when commitment clashes with circumstances or conditions in organizational management. This research is descriptive qualitative research that measures the concept of thinking from a questionnaire about the relationship of commitment to organizational management so that it will get an idea of the meaning of commitment in the organization. Data collection using questionnaires with interview methods with respondents to explore information about the process of forming commitments and to get how much perspective on commitments. In addition, this study also uses observation methods to get an overview of what happens about the respondents' perspective on the meaning of commitment and its application to the organization, whether it is limited to encouragement in the implementation of organizational management or extends to responsibility for organizational management with risks that occur when it clashes with non-conformities. The conclusion obtained is: that commitment is a meaning that serves as a positive encouragement that aims to arouse work passion in achieving the goals of the organization. Commitment cannot be made something to blame when the final results achieved do not follow organizational expectations because the nature of commitment is only as a positive bait and only as one's self-motivation to build enthusiasm in achieving organizational goals. The need for a policy is an effort used to bridge situations that are not by the actual situation so that the role of commitment will still be maintained to lead to the planned final results. Without rules, a commitment can still be implemented, because a commitment is an affirmation or expression conveyed to others as an effort to convince themselves of their sincerity or seriousness in acting. Even without rules, social sanctions will still occur if the perpetrators of the commitment do not carry out the consequences. On the other hand, with the application of written rules, a commitment will be more effective in its implementation because the rules are an order that must be obeyed and carried out and accompanied by written sanctions Keywords: Commitment, Organization, Management, Management